1990
DOI: 10.1073/pnas.87.19.7722
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tyrosine phosphorylation prevents T-cell receptor-mediated signal transduction.

Abstract: The binding ofantigen to the multicomponent T-cell receptor (TCR) activates several signal transduction pathways via coupling mechanisms that are poorly understood. One event that follows antigen receptor engagement is the activation of inositol phospholipid-specific phospholipase C (PLC). TCR activation by antigen, lectins, or anti-TCR monoclonal antibody has also been showu to cause increases in tyrosine phosphorylation of TCR-C and other substrates, suggesting stimulation of protein tyrosine kinase (PTK) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
216
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(226 citation statements)
references
References 21 publications
9
216
0
1
Order By: Relevance
“…Similarly to these results, a differential effect of herbimycin A has previously been reported for the T-cell receptor-and PMA-mediated IL-2 production and IL-2 receptor expression in human peripheral T cells [29].…”
Section: Resultssupporting
confidence: 87%
“…Similarly to these results, a differential effect of herbimycin A has previously been reported for the T-cell receptor-and PMA-mediated IL-2 production and IL-2 receptor expression in human peripheral T cells [29].…”
Section: Resultssupporting
confidence: 87%
“…Previous studies have reported that prolonged (4 -16 h) treatment of cells with inhibitors of Hsp90 reduces the levels of Lck protein and kinase activity (June et al, 1990;Hartson et al, 1996). To determine whether Hsp90 activity is required for the synthesis of Lck or for maintenance of the mature protein, we examined the effect of Hsp90 inhibition on newly synthesized and mature Lck separately.…”
Section: Hsp90 Activity Is Required For Synthesis But Not For Maintementioning
confidence: 99%
“…Engagement of the TCR with antigen or anti-TCR monoclonal antibody induces at least three rapid biochemical changes that are of probable significance in signal transduction: an increase in the level of free intracellular calcium (Imboden et al 1985), the activation of protein kinase C (Chen et al 1986, Nel et al 1986, and an increase in tyrosine phosphorylation (Campbell & Sefton 1990, June et al 1990, Lane et al 1990.…”
Section: Discussionmentioning
confidence: 99%
“…It is cur-rently accepted that the signal transduction cascade is initiated by activation of protein tyrosine kinases (PTK) (Samelson et al 1986, June et al 1990, Chan et al 1994, which results in the phosphorylation of a number of cellular proteins, such as phospholipase C-g1 (PLC) (Weiss et al 1991). Activated PLC, in turn, catalyzes the hydrolysis of membrane phosphoinositides to generate inositol 1,4,5-trisphosphate (IP 3 ) and diacylglycerol, second messengers responsible for the mobilization of cytoplasmic free calcium (Ca 2+ ) and activation of protein kinase C (PKC), respectively (Imboden et al 1985).…”
mentioning
confidence: 99%